Pengaruh Kompetensi Dan Pelatihan Terhadap Kinerja Guru Pada Madrasah Aliyah Negeri (MAN) Sampang Dengan Disiplin Kerja Sebagai Variabel Intervening - Choirul Anam; Ruddy Winarko; Wasis Budiarto (Journal of Management and Creative Business, 2023)
Choirul Anam, 2023. The Influence of Teacher Competence and Training on Teacher Performance at the State Islamic Senior High School (MAN) of Sampang with Work Discipline as an Intervening Variable. Postgraduate Program at Wijaya Putra University, Surabaya. The type of this research is explanatory research, the approach used is a quantitative approach and is complemented by a qualitative approach, the research sample is 69 people. The analysis tool uses Smart PLS (Partial Least Square). Research objectives: 1) To describe how teachers' competence, training, work discipline and teacher performance in the State Madrasah Aliyah (MAN) Sampang. 2) To test and analyze whether teacher competency has a significant effect on teacher performance in the State Madrasah Aliyah (MAN) Sampang. 3) To test and analyze whether teacher competence has a significant effect on teacher work discipline in the State Madrasah Aliyah (MAN) Sampang. 4) To test and analyze whether the training has a significant effect on the work discipline of teachers in the State Madrasah Aliyah (MAN) Sampang. 5) To test and analyze whether work discipline has a significant effect on teacher performance at the State Madrasah Aliyah (MAN) Sampang. 6) To test and analyze whether work discipline has a significant effect on teacher performance at the State Madrasah Aliyah (MAN) Sampang. 7) To test and analyze whether teacher competence has an indirect effect on teacher performance at the State Madrasah Aliyah (MAN) Sampang through work discipline. 8) To test and analyze whether the training has an indirect effect on teacher performance at the State Madrasah Aliyah (MAN) Sampang through work discipline. The results showed that: 1) Teacher competence has a significant positive effect on teacher performance. 2) Teacher competence has a significant positive effect on work discipline. 3) Training has a significant positive effect on work discipline. 4) Training has a significant positive effect on teacher performance. 5) Work discipline has a significant positive effect on teacher performance. 6) Teacher competence has a significant positive effect on teacher performance with work discipline as an intervening variable. 7) Training has a significant positive effect on teacher performance with work discipline as an intervening variable.